Clinical study to evaluate the efficacy of Commiphora muku (Muqil) on thyroid function in hypothyroidism - Iqbal, Arsheed; Habib, Arif; Ahmad, Sheikh Zahoor; Afzal, Asma; Jan, Afroza; ., Huma; Shah, Arjumand (International Journal Of Community Medicine And Public Health, 2023)
Background: Hypothyroidism is a common endocrine disorder in which there is deficient production of thyroid hormone. Even though hormone replacement therapy is the mainstay treatment of hypothyroidism, but due to adverse effects on long term use, safe and effective Unani herbal drugs need to be researched. A decrease in serum concentrations of thyroid hormone causes an increased secretion of thyroid stimulating hormone (TSH), thus resulting in elevated serum TSH concentration. Methods: The methods used to determine thyroid dysfunction are still serum thyroid stimulating hormone and the main circulating thyroid hormones thyroxine and triiodothyronine either as total or estimated free concentrations, and it is indeed the improved assay sensitivities and specificities that have made it possible to diagnose these milder forms. TSH, T3 and T4 with safety parameters tests were done before treatment and after completion of treatment in both the groups in order to make the proper diagnosis, to exclude other systemic ailments and to assess the efficacy/safety of the proposed herbal drug. Results: The effects of test drug on lowering the raised serum TSH are attributed to the thyroid activities of the test drug which shoes highly significance p<0.01 before and after intervention. In respect of thyroxin there were no significant results between the test and control group. Conclusions: The study concluded that the efficacy of Commiphora mukul (Muqil) on thyroid function was designed to explore the role of Unani herbal drugs in the management of hypothyroidism on Unani principles is effective, safe and cost effective.